Faktor – Faktor yang Berkaitan dengan Pemberian Vitamin A pada Balita di Posyandu Wilayah Kerja Puskemas Aek Parombunan Kota Sibolga Provinsi Sumatera Utara Tahun 2024 - Irayanti Manalu; Zulkarnain Batubara; Marta Armita Silaban; Rosmega Rosmega (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Health problems related to nutrition due to lack of intake of vitamin A obtained from food in the body due to metabolic disorders in the body, especially in toddlers in Aek Parombunan Posyandu Sibolga city, therefore the aim of this research is to analyze the factors related to giving Vitamin A to Toddlers at posyandu in Aek Parombunan, Sibolga City, North Sumatera Province in 2024. This type of research is quantitative with a cross sectional study design. The research was conducted in February-June 2024 with a sample of 32 toddlers using Random Sampling Technique. The population in this study were all mothers with toddlers (6-59 months) who visited the Kelambir Village posyandu February – June 2024. Data collection technique was questionnaire. The data analysis used was univariate and bivariate analysis with the Chi Square test. The research results showed that variables related to giving vitamin A to toddlers were the mother's knowledge variable value (p=0.006) and the toddler's activeness variable in visiting the posyandu value (p=0.018). Meanwhile, the variable that is not related is the role of value cadres (p=0.201). The conclusion is that there is a relationship between maternal knowledge and toddlers' activeness in visiting the posyandu with the provision of Vitamin A to toddlers at the posyandu in Aek Parombunan, Sibolga City, North Sumatera Province in 2024.